Botulinum Toxin Injection for Spastic Scapular Dyskinesia After Stroke: Case Series - Hou, Saiyun (Medicine (Baltimore), 2015)
Spastic scapular dyskinesia after stroke is rare, which causes impaired shoulder active range of motion (ROM). To date, there has been no report about botulinum toxin injection to spastic periscapular muscles. This study presents botulinum toxin A injection for management of spastic periscapular muscles after stroke in 2 cases. This is a retrospective study of 2 cases of spastic scapular dyskinesia after stroke. Spasticity of periscapular muscles including rhomboid and lower trapezius was diagnosed by physical examination and needle electromyographic study. Botulinum toxin was injected into the spastic periscapular muscles under ultrasound imaging guidance. During the 3-week follow-up visit after injection, both patients showed increased shoulder active ROM, without any sign of scapular destabilization. The results suggest that botulinum toxin injection to spastic periscapular muscles can increase shoulder active ROM without causing scapular destabilization in patients with poststroke spastic scapular dyskinesia.